IMPROVING THE SPEECH SKILLS OF STUDENTS OF NON-PHILOLOGICAL DIRECTIONS OF EDUCATION IN THE CONTEXT OF SOCIOCULTURAL COMPETENCE - Nuritdinovna, Ilhamova Iroda (International Journal of Psychosocial Rehabilitation, 2020)
This article is written for the purpose of the study is to improve the speech skills of students of non-philological areas of education in the context of sociocultural knowledge. The following research tasks are defined and their solutions are developed: to improve the speech skills of students of non-philological areas of education in the context of sociocultural competence based on web-quest technologies; to improve the metacognitive components of innovative technologies aimed at the development of speech skills of students of non- philological areas of education in the context of sociocultural competence; to improve the model for the development of speech skills of students of non-philological areas of education in the context of sociocultural competence; to develop guidelines for the development of speech skills of students of non-philological areas of education in the context of sociocultural competence.